2015
DOI: 10.1002/cplu.201402456
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Dependent Immobilization of a Tungsten Peroxo Complex That Catalyzes the Hydroxymethoxylation of Olefins

Abstract: A tungsten peroxo complex stabilized by the bidentate picolinato ligand has been synthesized and then immobilized successfully on imidazole‐functionalized silica. The immobilized tungsten‐based catalyst was employed as an efficient catalyst for the one‐pot synthesis of β‐alkoxy alcohols from olefins and methanol with H2O2. Regarding the catalyst evaluation and the results of characterization by the various methods, it was demonstrated that the immobilization of tungsten peroxo complex was highly temperature‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…β‐alkoxy alcohols are used as valuable organic solvents, finechemicals, versatile synthons, and pharmaceutical intermediates . The main strategy to synthesize β‐alkoxy alcohols is a two‐step reaction that epoxidation of olefins and sequential alcoholysis of epoxides under acidic conditions .…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…β‐alkoxy alcohols are used as valuable organic solvents, finechemicals, versatile synthons, and pharmaceutical intermediates . The main strategy to synthesize β‐alkoxy alcohols is a two‐step reaction that epoxidation of olefins and sequential alcoholysis of epoxides under acidic conditions .…”
Section: Introductionsupporting
confidence: 88%
“…By analogy with the previous reports, mechanism of the tandem reaction is shown in Scheme . As already described above, the one‐pot direct conversion of styrene into β‐alkoxy alcohol requires two catalytic centers to complete the two different parts of reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Similar POM-ILs (Figure ) with poly­(ethylene glycol)-functionalized alkylimidazolium cations and heteropolyacids as anion were further reported by Hou and co-worker. Due to the special thermo-regulated behavior, they have proved to be efficient catalysts both in esterification and epoxidation reactions. Interestingly, silica immobilized tungsten peroxo complex was also proven to be thermoresponsive by the same group in 2015 . During the one-pot synthesis of alkoxy alcohols from olefin and methanol with H 2 O 2 , it was found that the catalytically active tungsten peroxo complex can dissociate from silica under the reaction temperature, resulting in a homogeneous reaction.…”
Section: Thermomorphic Systems Based On Ionic Liquids (Ils)mentioning
confidence: 99%
“…Interestingly, silica immobilized tungsten peroxo complex was also proven to be thermoresponsive by the same group in 2015. 282 During the one-pot synthesis of alkoxy alcohols from olefin and methanol with H 2 O 2 , it was found that the catalytically active tungsten peroxo complex can dissociate from silica under the reaction temperature, resulting in a homogeneous reaction. However, the soluble W-based species was anchored robustly on silica as the temperature was decreased to 0 °C.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation